Understanding Attendees’ Feedback and Outcomes from the Diploma in Agricultural Extension Services for Input Dealers (DAESI) Training Programme - Chitra Das (Archives of Current Research International, 2024)
Input dealers serve as a key source of agricultural information for farmers at the village level, functioning as a one-stop shop. Therefore, they need to be well-versed in location-specific crop production technologies related to broad-based agriculture and proficient in managing agricultural inputs. This expertise ensures they can offer accurate advice to farmers dealing with field issues. In this context, MANAGE introduced the Diploma in Agricultural Extension Services for Input Dealers (DAESI), a significant national program by the Ministry of Agriculture and Farmers’ Welfare. This program aims to train agri-input dealers across the country, equipping them to serve as para extension workers and provide farmers with reliable technical knowledge. Ex-post facto cause to effect research design has been followed for the present study. This empirical study on the attendees’ perception and experiences of DAESI programme showcases not only their socio-economic profile of the input dealers undergoing training but also their insights on training programme package (satisfactorily good as a whole); their feedback on resource material and mode of delivery (suitable); their outlook of the facilitator of the programme (cooperative and favourable) as well as their experience regarding the activities performed during the training (satisfactory); and lastly the attendees’ perception regarding the objective to attend the DAESI Training Programme (amongst which majority of them attended the programme to either obtain certificate or to become a para-extension worker).The DAESI program is a trailblazing way that offers participants, who lack formal agricultural qualifications, a chance to acquire agricultural knowledge. Obtaining the diploma is a compulsory step for renewing their licenses, which drives many, particularly those with business interests, to enroll in the DAESI program. To enhance the DAESI training program, updating cost norms, incorporating digital learning, introducing refresher courses, tailoring the curriculum to local needs, strengthening public-private partnerships, increasing practical exposure, and promoting gender inclusivity could be followed.